MANAJEMEN PENGELOLAAN SAMPAH OLEH DINAS LINGKUNGAN HIDUP KOTA SURAKARTA - Eva Anggi Ariyani; Augustin Rina Herawati; Dyah Hariani (Journal of Public Policy and Management Review, 2022)
Environmental problems have now become a problem in all parts of the world Environmental waste problems affect human welfare and other survival. Garbage has now become a problem and a challenge in urban areas. This waste problem is increasing from year to year. The purpose of this study was to determine the management of waste management by the Surakarta City Environmental Service, to determine the driving and inhibiting factors in waste management in Surakarta City. This study uses the theory of Management G. R Terry, which looks at the management functions of planning, organizing, implementing and supervising. This study uses descriptive qualitative analysis by taking a case study at the Surakarta City Environmental Service. Data collection techniques were carried out by interviewing, library research, and documentation through primary and secondary data sources. The results showed that the management of waste management by the Surakarta City Environment Service had been carried out well from the planning, organizing, implementing, and monitoring stages. This is evidenced by several clear regulations, aspects of financing and implementation in accordance with the plan, although there are still some aspects that need to be improved, such as human resource problems and also due to limited land for waste management. The Surakarta City Environmental Service has an awareness that waste can be used as renewable energy so that it must be managed properly in order to provide a positive value for improving the welfare of the community.